Environmental Effects Determine the Structure of Potential β‐Amino Acid Based Foldamers. Issue 42 (29th June 2018) - Sussman, Fredy; Sánchez‐Pedregal, Víctor M.; Estévez, Juan C.; Balo, Rosalino; Jiménez‐Barbero, Jesús; Ardá, Ana; Gimeno, Ana; Royo, Miriam; Villaverde, M. Carmen; Estévez, Ramón J.
Abstract: This work shows that hybrid peptides formed by alternating trans ‐2‐aminocyclopentanecarboxylic acid ( trans ‐ACPC) and trans ‐2‐aminocyclohexanecarboxylic acid ( trans ‐ACHC) do not fold in the solvents typically used in the study of their homo‐oligomers. Only when the peptides are assayed in SDS micelles are the predicted helical structures obtained. This indicates that the environment could play an equally important role (as the backbone stereochemistry) in determining their fold, possibly by providing a sequestered environment. Abstract : Structural studies on a hybrid β‐amino acid oligomer have shown that the structure of β‐peptide foldamers depend substantially on solvent effects, and not just on the torsional backbone propensity of their amino acid components (see scheme).